ROLE OF GANDUSHA IN PITTAJA MUKHAPAKA (APHTHOUS ULCER) - A RANDOMIZED CONTROLLED TRIAL - L, Roopa; Fiaz, Shamsha; Laksmana Chary, Dingari; Yogitha M.R, Bali (International Journal of Ayurveda and Pharma Research, 2019)
Background: Pittaja Mukhapaka or the Aphthous ulcer is a painful and often recurrent inflammatory process of the oral mucosa that can appear secondary to various well-defined disease processes. Idiopathic recurrent aphthous stomatitis is referred to as recurrent aphthous stomatitis.Objectives: To evaluate the effect of Patoladi kashaya gandusha in Toda, Daha, Asyavairasyata and the pH of Pittaja mukhapaka (Aphthous ulcer) and to standardize the frequency of Gandusha (An Ayurvedic intervention).Design: This was a randomized controlled study with thirty patients divided into two groups, 15 in each. In Group A, Patoladi kashaya gandusha (gargling) was given once a day for 7 days and in Group B, Patoladi kashaya gandusha (gargling) was carried out twice a day for 7 days. After the completion of treatment, follow up was done once in fifteen days for a period of 2 months.Results: Statistically significant results were seen in reduction of Toda with p<0.001, Group A (61.53%) compared to Group B (81.81%), Daha with p<0.001 Group A (73.07%) compared to Group B (81.81%), Asyavairasyata with p<0.001 Group A (73.91%) compared to Group B (100%) and also in relieving the pH of saliva with p<0.001 and Group A (100%) compared to Group B (100%).Conclusions: Group B (Patoladi kashaya gandusha given twice a day) showed statistically significant results compared to Group A (Patoladi kashaya gandusha given once a day) in reduction of Toda, Daha, Asya vairasyata and the pH of Pittaja Mukhapaka (Aphthous ulcer).